AXMEDIS 2008 Proceedings of the 4th International Conference on Automated Solutions for Cross Media Content and Multi-Channel Distribution.Workshops, Panels and Industrial Applications - Delgado, Jaime; Nesi, Paolo; Ng, Kia (Proceedings e report, 2008)
The AXMEDIS International Conference series aims to explore all subjects and topics related to cross-media and digital-media content production, processing, management, standards, representation, sharing, protection and rights management, to address the latest developments and future trends of the technologies and their applications, impacts and exploitation. The AXMEDIS events offer venues for exchanging concepts, requirements, prototypes, research ideas, and findings which could contribute to academic research and also benefit business and industrial communities. In the Internet as well as in the digital era, cross-media production and distribution represent key developments and innovations that are fostered by emergent technologies to ensure better value for money while optimising productivity and market coverage.